Review on the health-promoting effect of adequate selenium status - Sun, Ying; Wang, Zhineng; Gong, Pin; Yao, Wenbo; Ba, Qian; Wang, Hui (Frontiers in Nutrition, 2023)
Selenium is an essential microelement involved in various biological processes. Selenium deficiency increases the risk of human immunodeficiency virus infection, cancer, cardiovascular disease, and inflammatory bowel disease. Selenium possesses anti-oxidant, anti-cancer, immunomodulatory, hypoglycemic, and intestinal microbiota-regulating properties. The nonlinear dose-response relationship between selenium status and health effects is U-shaped; individuals with low baseline selenium levels may benefit from supplementation, whereas those with acceptable or high selenium levels may face possible health hazards. Selenium supplementation is beneficial in various populations and conditions; however, given its small safety window, the safety of selenium supplementation is still a subject of debate. This review summarizes the current understanding of the health-promoting effects of selenium on the human body, the dietary reference intake, and evidence of the association between selenium deficiency and disease.